RESOLUSI KONFLIK PAKISTAN DAN INDIA DALAM PEREBUTAN WILAYAH KASHMIR DAN PELUANG MEDIATOR BAGI INDONESIA - Khairunnisa, Briliant Windy (Jurnal Ilmiah Widya Sosiopolitika; Vol 3 No 2 (2021): MEDIA, POLITIK, DAN PANDEMIDO - 10.24843/JIWSP.2021.v03.i02.p04, 2021)
Abstract The conflict between Pakistan and India on the border of the two countries in the dispute over the Kashmir region has been going on for years. Although many efforts have been tried to reconcile the two countries, the conflict continues to cause a lot of harm to the indigenous people of Kashmir which continues to this day. As a country that has good relations with Pakistan and India, Indonesia can be declared as a neutral country and has a large enough opportunity to become a mediator between the two countries as a conflict resolution effort. This article aims to discuss the efforts to resolve the conflict between Pakistan and India in the dispute over the Kashmir region and the opportunities that Indonesia has to become a mediator between the two countries. The research method in this study uses exploratory qualitative and data collection techniques in the form of literature studies based on secondary data. The results of the study indicate that Indonesia has an opportunity to become a mediator in the resolution of the Kashmir conflict. Keywords : Conflict Resolution, Pakistan-India Conflict, Kashmir, Indonesia, Mediator.